2013
DOI: 10.4103/2231-0746.110081
|View full text |Cite
|
Sign up to set email alerts
|

Psammomatoid type juvenile ossifying fibroma of mandible

Abstract: Juvenile ossifying fibroma (JOF) is a rare fibro-osseous neoplasm that arises within the craniofacial bones in individuals under 15 years of age, and these lesions are usually benign and tend to grow slowly. The psammomatous type of juvenile ossifying fibroma (PsJOF) mainly involves the bones of the orbit and paranasal sinuses, whereas the trabecular type commonly involves the jaws. We are presenting a case of PsJOF of ramus of mandible in a 7-years-old boy, which is an uncommon condition, and histologically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…It mostly occurs in first to second decade of life without any sex predilection . Common sites include the facial bones (85%), calvarium (12%), and mandibular region (10%) . The term JOF in WHO classification (2005) includes two histopathological variants—psammomatous and trabecular .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It mostly occurs in first to second decade of life without any sex predilection . Common sites include the facial bones (85%), calvarium (12%), and mandibular region (10%) . The term JOF in WHO classification (2005) includes two histopathological variants—psammomatous and trabecular .…”
Section: Discussionmentioning
confidence: 99%
“…Fibro‐osseous lesions of the jaw comprise a spectrum of diseases which include cement‐osseous dysplasia (COD), fibrous dysplasia (FD), and ossifying fibroma . Morphological differentiation among these individual entities is difficult and a combined clinico‐radiological correlation is essential for exact categorization.…”
Section: Introductionmentioning
confidence: 99%
“…However, different treatment modalities have been proposed depending on the size and invasion of adjacent tissue. Patil et al 7 and Banu & Palikat 2 reported that small neoplasms can be treated successfully by enucleation and curettage, while resection should be considered in cases of recurrence of the lesion or invasion of adjacent tissues and cavities. The authors also suggested that, in the absence of paresthesia and involvement of the lower mandibular border, a more conservative treatment can be planned.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblastic spindle cells constituted stroma with anastomosing areas of cellular condensation, garland like bony strands lined by plump osteoblasts and cement particles are usually present (13,14). Not much atypia or mitotic activity is seen (15). Diagnosis of juvenile ossifying fibroma could be ruled out because no spindle shaped fibroblasts or whorling pattern of cells or trabecular/psammomatoid osteoid matrix was seen.…”
Section: Discussionmentioning
confidence: 99%